Quantitative hepatitis B e antigen: a better predictor of hepatitis B virus DNA than quantitative hepatitis B surface antigen - Hudu, Shuaibu A.; Mohd Taib, Niazlin; Amin Nordin, Syafinaz; Saeed, Mohammed I.; Tan, Soek S.; Omar, Haniza; Shahar, Hamiza; Sekawi, Zamberi (Clinical Laboratory Publications, 2018)
Background: Hepatitis B surface antigen is usually secreted by infected hepatocytes in the form of subviral particles rather than infectious virions, while the hepatitis B e antigen originates from the core gene and is modified and secreted by hepatocytes into the circulation and functions as a marker of active viral replication. This study aimed to study the relationship between HBV DNA and quantitative hepatitis B surface and e antigen in Malaysian patients. Methods: A total of 82 chronic hepatitis B patients were recruited for this study from the Hepatology Department of Selayang Hospital. Quantitative hepatitis surface and e antigen was performed retrospectively on frozen plasma using enzyme linked immunosorbent assay according to the manufacturer's instructions. Hepatitis B viral DNA was extracted from all plasma samples and quantified using real-time PCR. Results: Quantitative hepatitis B surface and e antigens were found be high in 54.9% and 52.4% of the patients, respectively, while hepatitis B virus DNA level was high in 70.7%. The median of the viral load of HBV was 8,934.89 IU/mL and both hepatitis B surface and e antigens were also found to be high on average for qHBsAg (M = 5.19 IU/mL, SD ± 4. 33) and qHBeAg (M = 4.74IU/mL, SD ± 4.20), with qHBeAg being more strongly correlated to HBV DNA than qHBsAg (r = 0.893; p < 0.01). Conclusions: This study revealed HBeAg to be the most appropriate marker that correlates well with HBV DNA, thus not completely novel but confirmative, and related to the Malaysian situation.